EFEKTIVITAS PROGRAM KARTU PRA KERJA DI KOTA PEKANBARU - Wiwik Onya Hutabarat; Dadang Mashur (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The Pre-Employment Card Program is a program created by the ndonesian government in the form of training fee assistance to improve the competence of the workforce which is held throughout Indonesia. The target of the pre-employment card program is for job seekers, workers affected by termination of employment, and non-wage workers who need competency improvement. However, there are obstacles in the implementation of the Pre-Employment Card program in Pekanbaru City, such as the program targets that are still not appropriate and the participants' lack of interest in participating in the training. This study aims to determine the effectiveness of the pre-employment card program in Pekanbaru City. The theory used in this study is the theory of effectiveness by Budiani with four indicators, namely the accuracy of program targets, program socialization, program objectives, and program monitoring. This research method uses qualitative methods with data collection techniques based on observations, interviews, and documentation. The results of this study indicate that the effectiveness of the pre-employment card program in Pekanbaru City has not been effective both from the indicators of the accuracy of program targets, program socialization, program objectives and program monitoring. The factors that hinder the implementation of this program are the program is a program from the central government and the lack of public awareness.